2020
DOI: 10.1002/jbm4.10387
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Parathyroid Hormone Accelerates Stress Fracture Healing More Effectively Following Cessation of Bisphosphonate Treatment

Abstract: Parathyroid hormone (PTH) and bisphosphonates (BPs), including alendronate (ALN), have opposing effects on bone dynamics. The extent to which PTH remains effective in the treatment of stress fracture (SFx) in the presence of an ongoing BP treatment has not been tested. SFx was induced in 150 female Wistar rats, divided into five equal groups (n = 30). All rats were pretreated with ALN (1 μg/kg−1/day−1) for 14 days prior to SFx induction, followed by ALN cessation or continuation for the duration of the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
(133 reference statements)
0
1
0
Order By: Relevance
“…In 102 postmenopausal women with distal radial fractures, daily placebo, 20 µg teriparatide or 40 µg teriparatide (34 patients in each group) resulted in a shorter healing time with teriparatide 20 µg but not with 40 µg teriparatide, compared with placebo ( 18 ). Intermittent PTH accelerated stress fracture healing more effectively following cessation of bisphosphonate treatment ( 109 ).…”
Section: Pharmacologic Interventionsmentioning
confidence: 99%
“…In 102 postmenopausal women with distal radial fractures, daily placebo, 20 µg teriparatide or 40 µg teriparatide (34 patients in each group) resulted in a shorter healing time with teriparatide 20 µg but not with 40 µg teriparatide, compared with placebo ( 18 ). Intermittent PTH accelerated stress fracture healing more effectively following cessation of bisphosphonate treatment ( 109 ).…”
Section: Pharmacologic Interventionsmentioning
confidence: 99%
“…found that administration with the osteoanabolic parathyroid hormone (PTH) treatment promoted the recovery of bone stress injuries in the rodent model. 18 , 19 Inklebarger et al. showed that vitamin D supplementation stimulated the healing of the stress fracture for the individual with low vitamin D status.…”
Section: Introductionmentioning
confidence: 99%